A Study of Disclosures on Risk Management of Life Insurance Companies in India - Hariharan, B. R.; Sailaja, Vedala Naga; Patel, Kalp Vinodchandra (Indian Journal of Finance, 2017)
This study attempted to find out different reporting practices used by Indian life insurance companies for risk management and risk governance in their annual reports. The factors considered for assessing the quality of the disclosure were risk management framework, risk governance, the independence and profile of chief risk officer, risk policies they explained, and quality certification they have obtained. The study showed that there was a very wide variation in content of their disclosures although every company was following the same corporate governance guidelines of the Insurance Regulatory and Development Authority of India (IRDAI).